How girls fall behind on cognitive performance: quantile decomposition evidence from Andhra Pradesh, India - Nair, D (Young Lives, 2013)
Cognitive competence is a fragile construct and a range of factors influence whether individuals perform above or below their ability. Using rich longitudinal data collected by Young Lives from the state of Andhra Pradesh, India (2002-2009), this paper studies two cohorts of children at two points in time (at 5 and 8 years, and 12 and 15 years of age) and examines gender inequality in performance in language and math tests. It looks at the contribution of a rich set of explanatory variables to the gender gap from middle childhood through adolescence. Applying newly developed quantile estimation techniques in conjunction with traditional Blinder-Oaxaca decompositions, this paper examines the gender gap in test scores. I also examine the difference in change in scores over time for boys and girls. The evidence suggests that: (a) Gender differences at the mean mask substantial heterogeneity across quantiles. (b) Girls fall behind particularly in math by the age of 15. Even at 5 years, girls have no cognitive advantage in language or math – despite contrary evidence from other contexts. (c ) The largest gains experienced over the two rounds is by 15 year old boys in the 95th percentile of math performance (0.68 standard deviations), and the largest losses are by 15 year old girls at the median of math scores (-0.61 standard deviations). (d) A widening of the boy-advantage takes place over time and across quantiles for the younger cohort in language, and for the older cohort in math. (e) Unexplained effects contribute most to girls falling behind in math scores at 15 years of age – providing possible evidence of gender discrimination.(f) Child-level factors contribute the most to changes (explained and unexplained) in scores. This highlights the influence of characteristics such as self-efficacy on the relatively poor test performance of (the brightest) girls in the current context.